Very high cycle fatigue behavior of laser powder bed fusion additively manufactured Ti6Al4V alloy at elevated temperature - Peng, Haotian (2023)
The crack initiation mechanism of laser powder bed fusion (LPBF) Ti6Al4V was investigated at elevated temperature up to very high cycle fatigue (VHCF) regime. The competition concerning defect location is elaborated using the stress intensity factor range and Z-parameter model. Additionally, localized high stress near the defects is responsible for plastic strain localization in the non-prior α' region, following the grain refinement and fragmentation in the larger grains nearby, which is strongly associated with the formation of microcracks and fine granular area. Meanwhile, the process is facilitated by reducing dislocation resistance and activating multiple slip systems due to high temperature.